Experimental investigation of the cyclic pitch control on a horizontal axis wind turbine in diagonal inflow wind condition. (1st September 2017) - Sang, Le Quang; Takao, Maeda; Kamada, Yasunari; Li, Qing'an
Abstract: Offshore wind power has huge energy potential. For deep water areas, FOWTs (Floating Offshore Wind Turbines) are sensitive to large oscillations due to the aerodynamic force of wind and the hydrodynamic force of wave. In the natural environment, the wind is usually unstable and characterized by the diagonal inflow wind. In this study, the potential of alleviating blade load variations induced by the cyclic pitch control evaluated under the condition of the diagonal inflow wind. An experiment in an open wind tunnel was performed to investigate the effect of the diagonal inflow wind on the aerodynamic forces of FOWTs. A two-bladed downwind FOWT with a diameter of 1.6 m used for this experiment. The forces and moments applied to the entire wind turbine were measured by a six-component balance. A swash plate used to adjust the pitch angle in the cyclic pitch control. From the experimental results, the average value of the aerodynamic load acting on the rotor face in the diagonal inflow wind condition at phase angle of ξ  = 60° equals the moment coefficient in the optimum operating condition at the front inflow wind. The load change on yaw system can be controlled by cyclic pitch control method. Highlights: Swash plate is used to adjust the blade pitch angle. Aerodynamic force of FOWT is investigated in the diagonal inflow wind condition. Power and thrust coefficients were almost constant regardless of the amplitude of the periodic change. Cyclic pitch control showed the possibility of reducing the load vibrations acting on the wind turbine. Load change on yaw system can be controlled by cyclic pitch control.